Sprachpflege und Sprachnormierung in Frankreich am Beispiel der Fachsprachen vom 16. Jahrhundert bis in die Gegenwart - Mayer, Martina (Studien des Interdisziplinären Frankreich-Schwerpunkts der Universität Innsbruck, 2013)
This book is now analyzing chronologically from inserting first spoke of nursing efforts in the 16th century to the ministerial terminology commissions of the 21st century, the most important key moments of language maintenance and language standardization in France.